Danske regeringers ansættelsesudvalg 1977-2017 - Nielsen, Peter Heyn (Historisk Tidsskrift, 2018)
The Appointments Committee in Danish Governments Within the field of Danish political science, the daily operations of government is a relatively unexplored subject; the Danish Government’s Appointments Committee, in particular, has never been the main focus of academic study. This is paradoxical, considering the fact that it is a well-established institution within the Danish political system. Every government in Denmark since 1977 has made use of such a committee. This article seeks to fill the gap by providing insight into the role and significance of this committee in the various governments since its creation. Analysis of a large selection of documents and elite interviews yields the conclusion that the committee has contributed to the solid centralisation of power within the Danish government, notably in the Prime Minister’s Office and the Ministry of Finance.